The Influence of Work Motivation, Organizational Climate and Leadership Style on Employee Job Satisfaction at PT. XYZ - Kartini, Tini; Jailani, M. Rachmat; Gemina, Dwi (West Science Interdisciplinary Studies, 2023)
This study aims to analyze the direct and positive influence of work motivation, organizational climate, and leadership style on employee job satisfaction, both partially and simultaneously. The research design used was descriptive and verificative. The sampling method used is a saturated sampling method, with a total of 40 respondents. The subject of this study was an employee of PT XYZ. The object of this study is work motivation, organizational climate, leadership style, and employee job satisfaction. The tools used are path analysis, multiple correlation analysis, coefficient of determination analysis and hypothesis testing with F test and t test. The results showed that work motivation, organizational climate, and leadership style on employee job satisfaction had a direct and positive influence both partially and simultaneously. If the company wants to have a high level of job satisfaction, employees must be given a boost in the form of motivation, a comfortable, supportive, and fulfilling organizational climate and have leaders who have an effective leadership style in accordance with employee needs. This research can be useful as advice and more understanding, to apply an effective leadership style it will play a good role for work motivation, organizational climate and employee job satisfaction.